Enhancing Tolerance and Cultural Diversity through Multicultural Education Management - Hartinah, Hartinah; Riantika, Tiara Pajri; Safira, Nur (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the management of multicultural education at SMP Negeri 3 Sorong City to increase tolerance and embrace cultural diversity among students. The research method used is descriptive and qualitative. Data collection techniques are carried out through interviews, observation, and documentation. The research results show that the multicultural education management implemented at SMP Negeri 3 Sorong City is diverse in its forms and has produced tolerance values in its students. Through various multicultural education activities in the learning process and educational environment, students are instilled with multicultural values to be tolerant and respectful of fellow students, even though they are of different ethnicities, cultures, and religions. Multicultural education can significantly influence students' attitudes towards tolerance and cultural diversity by developing an inclusive curriculum, teacher training, integration of multicultural values in school activities, and character development programs. This research indicates that implementing effective multicultural education strategies in schools can contribute significantly to increasing tolerance and respect for cultural diversity among students, thereby encouraging social cohesion and unity in a diverse society like Indonesia.